The giver - Lowry, Lois. (New York : Dell Laurel-Leaf, 2002)
Given his lifetime assignment at the Ceremony of Twelve, Jonas becomes the receiver of memories shared by only one other. He then learns the terrible truth about the Community.
"Readers circle"--Cover.
"Reprinted by arrangement with Houghton Mifflin Company"--T.p. verso.
"RL 4.5"--T.p. verso.
Includes a reader's guide.
Wilson's Children.
Wilson's Junior High School.
Keywords: Coming of age -- Fiction; Memory -- Fiction; Science fiction; Bildungsromans; Memory -- Fiction; Science fiction